TECNOLOGIAS INOVADORAS DE APOIO AO TRATAMENTO DE QUEIMADURAS EM CRIANÇAS - Zinhani, Mateus Claudio (2023)
Work is part of the Sustainable Development Goals, especially Goal 3: “Ensure healthy lives and promote well-being for all at all ages”, as well as the Ministry of Health’s Research Priorities Agenda, Axis 4 “Development of Technologies and Innovation in Health” and Axis 14 “Maternal and Child Health” and the targets set by the Digital Health Strategy for Brazil 2020-2028. The study is also part of the Project “Systematization of care and technological innovation in Nursing”, Thematic Area “Technology and Innovation in Nursing”, contemplated by the CAPES/COFEN Agreement Edital 08/2021. In an attempt to expand knowledge and practices related to burns in children and to foster new support technologies for treatment and healing, the project aims to Objectives: To identify in the national and international literature the cellulose acetate polymers used in the healing of burns in children; Analyze knowledge and train caregivers on the best conduct in the event of burn injuries in children; and to describe the process of developing an application to support the care and treatment of burns in children for health professionals and caregivers in general. Methodological path: It was carried out in sequential stages, between April/2022 and November/2023, using specific agile techniques and tools for each of the objectives previously listed. The work was carried out in cooperation with various areas of institutional knowledge: Nursing, Biomedical Engineering, Information Systems, Nanosciences, Innovation Environment. Results: Few published articles were found addressing the use of non-adherent dressings with antimicrobial potential. In the online survey carried out, the research process showed that more than half of the informants (53%) responded affirmatively to the presence of burn injuries in children up to two years old. This result alone demonstrates the relevance of this study and the importance of inducing prospective technologies and public policies that cover the different pediatric ages and social classes. Called “HEAL - Everything about healing”, the application developed demonstrates accessibility, feasibility and reliability in providing agile and safe information for the care and treatment of burns in children. Final considerations: A lack of studies on cellulose polymers used in the healing of burns in children was identified, which opens up space for the production of new technologies in this area of knowledge. The occurrence of burn injuries in children, based on the investigative study, shows the persistence of empirical thinking and acting about their immediate treatment, as it reflects a practice passed down from parents to children. With this in mind, HEAL app to support the care and treatment of burns in children is functional and has the potential to provide agile, effective and safe support to health professionals and caregivers in general. Product and its applicability: “HEAL - All about healing” app has the potential to impact on the nurses’ work process by optimizing human and material resources, speeding up the healing process, reducing the child’s hospital stay and, especially, by introducing a new technology to the market.